Rare Cases of Pediatric Vasoactive Intestinal Peptide Secreting Tumor With Literature Review: A Challenging Etiology of Chronic Diarrhea - Pai-Jui Yeh; Shih-Hsiang Chen; Jin-Yao Lai; Ming-Wei Lai; Cheng-Hsun Chiu; Hsun-Chin Chao; Shih-Hsin Chen; Ren-Chin Wu; Chao-Jan Wang; Chien-Chang Chen (Frontiers Media S.A., 2020)
Vasoactive intestinal peptide (VIP) secreting tumor (VIPoma) is a rare disease, presenting with profuse diarrhea, electrolyte imbalance, and possibly fatal outcome. The diagnosis and treatment are challenging, and no consensus guideline of management is available. The pediatric incidence remains unclear. This study comprises two pediatric case reports from a tertiary center and a literature-based case series investigating the characteristics among children. The two reported cases both presented with severe diarrhea and laboratory abnormalities, including electrolyte imbalance and elevated plasma VIP level. Case 1 received several imaging investigations, partial pancreatectomy, octreotide, and everolimus, reflecting her complicated and refractory course. Case 2 underwent total excision of suprarenal ganglioneuroblastoma, and the clinical response was significant. In both cases, varied degrees of symptomatic control, reduced plasma VIP level, and correction of electrolyte imbalance were achieved. A literature review-based case series analyzed 45 pediatric cases retrieved from the PubMed database until December 31, 2019. Demographics, clinical features, diagnostic modalities, treatments, and outcomes were presented.